Strategic Doing : Ten Skills for Agile Leadership /: Ten Skills for Agile Leadership. (2019) - Morrison, Edward; Hutcheson, Scott; Nilsen, Elizabeth; Fadden, Janyce; Franklin, Nancy
No abstract available